2019
DOI: 10.1039/c9nr02781e
|View full text |Cite
|
Sign up to set email alerts
|

Organic nanoparticles with ultrahigh stimulated emission depletion efficiency for low-power STED nanoscopy

Abstract: We prepared a STED probe with ultrahigh stimulated emission depletion efficiency for low-power STED nanoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…For example, SiNPs doped with the Atto647N dye showed STED power requirement (100∼400 MW/cm 2 ) similar to that of the bare dyes (Tavernaro et al, 2017). Meanwhile, SiNPs doped with specially designed fluorophores (non-SOC (Liang et al, 2020) or non-ACQ (Man et al, 2019)) showed an ultralow I sat of ∼10 -1 MW/cm 2 .…”
Section: Saturation Intensitymentioning
confidence: 95%
See 4 more Smart Citations
“…For example, SiNPs doped with the Atto647N dye showed STED power requirement (100∼400 MW/cm 2 ) similar to that of the bare dyes (Tavernaro et al, 2017). Meanwhile, SiNPs doped with specially designed fluorophores (non-SOC (Liang et al, 2020) or non-ACQ (Man et al, 2019)) showed an ultralow I sat of ∼10 -1 MW/cm 2 .…”
Section: Saturation Intensitymentioning
confidence: 95%
“…For SiNPs, their surficial Si-OH groups are not very reactive with most linkage groups (carboxyl, amine, etc.). Therefore, the functionalization of SiNPs is mostly performed through silane linkers like APTES before further modification with functional molecules by amidation (Schubbe et al, 2010;Schübbe et al, 2012;Man et al, 2019). This might lead to an increase in particle size during the modification, altering the biodistribution of these probes, especially for smaller particles.…”
Section: Functionalizing Methodsmentioning
confidence: 99%
See 3 more Smart Citations